The Impact of Online-Based Learning and Learning Environment on Students Outcome and Motivation - Iis Sujarwati; Reza Rezita (International Conference on Science, Education, and Technology, 2022)
Many factors can influence the process of learning activities and students’ motivation to learn such as student abilities, student circumstances, student environmental conditions, and dynamic elements in learning. This study aimed to decide the impact of online-based learning and the learning environment on the students’ outcomes and motivation as well. Descriptive correlational research was applied in this study. The 70 students majoring in TKJ grade X of SMKN 3 Kota Bengkulu, while the sample was 35 students became the population of this study. A set of questionnaires was used as the instrument. The data were analyzed by using IBM SPSS Version 26. The result of the study has shown that online-based learning affected learning motivation significantly. Besides, the learning environment also had a high effect on learning motivation. The last, the statistic displayed that online-based learning affected students learning outcomes. However, there was no significant influence between the learning environment and learning outcome.